SOCIO-ECONOMIC FACTORS INFLUENCING THE PROSPERITY OF TOBACCO FARMERS IN PROBOLINGGO REGENCY: A BUSINESS MANAGEMENT PERSPECTIVE - Ndau, Wensislaus Arman; Patiung, Markus; Wisnujati, Nugrahini Susantinah (PROCURATIO: Jurnal Manajemen & Bisnis, 2024)
The income of tobacco farmers in Probolinggo Regency is often unstable due to fluctuations in the prices of production factors and tobacco products, impacting their earnings and socio-economic conditions. The objectives of this study were: (1) to analyze the income of tobacco farmers; (2) to identify the factors influencing their income; and (3) to examine their social conditions. The data analysis method employed was multiple regression analysis. The results of the study revealed that: (1) the average income of tobacco farmers in Probolinggo Regency is IDR 18,540,000 per hectare per planting season, with an R/C ratio of 1.6; (2) the factors influencing the income of tobacco farmers include the prices of seeds, urea, ZA (ammonium sulfate), and pesticides; (3) 83% of the tobacco farmers own their houses, which are made of permanent materials. Common household electronic items owned by the farmers include refrigerators, televisions, and mobile phones. Regarding transportation, 57% of the farmers use bicycles, 28% use motorcycles, and 14.29% use cars to commute to work and take their children to school. The average family size is three members, consisting of two children and one spouse. Tobacco farmers feel comfortable in their environment, as evidenced by their active participation in activities such as repairing irrigation systems, cleaning the surroundings, and building worship facilities and social spaces to foster community relationships. This indicates that the socio-economic conditions of tobacco farmers are adequate and prosperous.